Communication is a two-way street: Analyzing practices undertaken to systematically transfer audit research knowledge to policymakers - Salterio, Steven E.; Hoang, Kris; Luo, Yi (Accounting, Organizations and Society, 2021)
Audit academics and policymakers express ongoing concerns about limited knowledge transfer between audit research and policymaking. We use theory-based knowledge transfer norms to evaluate eight practices used by audit academics to transfer research knowledge to policymakers. The discontinued PCAOB-AAA Auditing Section “Research Synthesis Project” came closest to enacting these theory-based knowledge transfer norms. Hence, we examine why those involved in that project did not follow these norms. Interviews with project authors reveal that their review creation approach anchored on the traditional academic literature review, and insufficiently adjusted it to meet the goal of communicating audit research evidence to policymakers. However, interviews with PCAOB project liaisons indicate that policymakers were engaged with and found value in the review creation process. Thus, we analyze PCAOB rulemaking documents for evidence that policymakers valued and used the project’s reviews in their policymaking. Over the project’s duration, we find increasing citations of research to the reviews themselves and to a broader set of academic research. Our findings of knowledge transfer occurrence in this project warrant further research on the efficacy of mobilizing audit research via research syntheses. We also show how several current audit domain knowledge transfer practices can be combined with the research syntheses approach leading to systematic effective knowledge transfer to policymakers.